2013
DOI: 10.4103/2230-8229.114774
|View full text |Cite
|
Sign up to set email alerts
|

Discharge against medical advice from Neonatal Intensive Care Unit: 10 years experience at a University Hospital

Abstract: Background:Discharging patients against medical advice is a problem of every age-group. However, because of their physiological vulnerability, the risk for the neonatal population is greater when discharged against medical advice (DAMA). This article is a study of the prevalence of the problem, the possible causes and/or risk factors.Materials and Methods:A retrospective review of 10 years of medical records of neonates discharged against medical advice from a Neonatal Intensive Care Unit (NICU) at a universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 5 publications
5
22
0
Order By: Relevance
“…This finding corroborates with other studies in pediatric [7, 9, 11] as well as neonatal populations [12, 13]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding corroborates with other studies in pediatric [7, 9, 11] as well as neonatal populations [12, 13]. …”
Section: Discussionsupporting
confidence: 93%
“…DAMA not only raises clinical, ethical, and legal issues for the treating physician [4] but also leads to adverse health outcomes thereby burdening the health system even more [5]. There have been few attempts by developing economies to document the extent of the problem as well as the reasons behind DAMA in pediatric population [611] and neonates [12, 13]. The studies in pediatric populations indicated that the problem is more prevalent in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Among the CALD groups, families of neonates were also found to be more likely to DAMA than families of children from other age groups, although this was not explored further in the dataset. Previous research has identified reasons for this observation, including children delivered vaginally with early ambulation of their mothers, families’ duty to care for other children at home and their false impressions that the child had improved 6 23…”
Section: Discussionmentioning
confidence: 99%
“…Similar difficulties were also experienced by immigrants from non-English speaking countries who were identified as CALD. When attending EDs in Australia, only 36% of patients who had limited English proficiency were provided trained interpreters 23. In the paediatric setting, 26% of CALD parents identified language as the single greatest barrier to accessing healthcare in the USA 24…”
Section: Discussionmentioning
confidence: 99%
“…Congenital malformations, the most common neonatal surgical diseases, are a leading cause of mortality and morbidity in the neonatal period and infancy besides labor associated problems like asphyxia and prematurity ( 2 ). Approximately 2.5–5% of all neonates have at least one anatomical malformation ( 3 ), but the spectrum of this heterogeneous group of diseases is very wide.…”
Section: Introductionmentioning
confidence: 99%